Factors driving structure of natural and anthropogenic forest edges from temperate to boreal ecosystems. (14th February 2016) - Esseen, Per‐Anders; Hedström Ringvall, Anna; Harper, Karen Amanda; Christensen, Pernilla; Svensson, Johan
Abstract: Questions: What factors control broad‐scale variation in edge length and three‐dimensional boundary structure for a large region extending across two biomes? What is the difference in structure between natural and anthropogenic edges? Location: Temperate and boreal forests across all of Sweden, spanning latitudes 55–69° N. Methods: We sampled more than 2000 forest edges using line intersect sampling in a monitoring programme (National Inventory of Landscapes in Sweden). We compared edge length, ecosystem attributes (width of adjacent ecosystem, canopy cover, canopy height, patch contrast in canopy height, forest type) and boundary attributes (profile, abruptness, shape) of natural edges (lakeshore, wetland) with anthropogenic edges (clear‐cut, agricultural, linear disturbance) in five regions. Results: Anthropogenic edges were nearly twice as abundant as natural edges. Length of anthropogenic edges was largest in southern regions, while the abundance of natural edges increased towards the north. Edge types displayed unique spectrums of boundary structures, but abrupt edges dominated, constituting 72% of edge length. Anthropogenic edges were more abrupt than natural edges; wetland edges had the most gradual and sinuous boundaries. Canopy cover, canopy height, patch contrast and forest type depended on region, whereas overall boundary abruptness and shape showed no regional pattern. Patch contrast was related to temperature sum (degree days ≥ 5 °C), suggesting that regional variability can be predicted from climate‐controlled forest productivity. Boundary abruptness was coupled with the underlying environmental gradient, land use and forest type, with higher variability in deciduous than in conifer forest. Conclusions: Edge origin, land use, climate and tree species are main drivers of broad‐scale variability in forest edge structure. Our findings have important implications for developing ecological theory that can explain and predict how different factors affect forest edge structure, and help to understand how land use and climate change affect biodiversity at forest edges. Abstract : Forest edges are ubiquitous landscape elements with important functions in both natural and man‐dominated ecosystems. We estimated edge length, ecosystem and boundary attributes from a sample of >2000 edges (lakeshore, wetland, agricultural, clearcut, linear) across Sweden. Our study increases our understanding of factors affecting broad‐scale variability in forest edge structure, and provides an important contribution for a comprehensive theory on edges.